2008
DOI: 10.1002/cyto.a.20657
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tumor cell dissemination patterns in preclinical models of cancer metastasis using flow cytometry and laser scanning cytometry

Abstract: The inability to sensitively detect metastatic cells in preclinical models of cancer has created challenges for studying metastasis in experimental systems. We previously developed a flow cytometry (FCM) method for quantifying circulating tumor cells (CTCs) in mouse models of breast cancer. We have adapted this methodology for analysis of tumor dissemination to bone marrow (BM) and lymph node (LN), and for analysis of these samples by laser scanning cytometry (LSC). Our objective was to implement these metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 69 publications
2
38
0
Order By: Relevance
“…5 D and E). Together, these data support that both MMTV-Met cells introduced via the tail vein bypass the normal metastatic cascade and are delivered directly to the lung, only rarely being detected in other organs (42)(43)(44). Notably, daily treatment of injected mice with the orally available MET inhibitor Crizotinib (45 mg·kg…”
mentioning
confidence: 60%
“…5 D and E). Together, these data support that both MMTV-Met cells introduced via the tail vein bypass the normal metastatic cascade and are delivered directly to the lung, only rarely being detected in other organs (42)(43)(44). Notably, daily treatment of injected mice with the orally available MET inhibitor Crizotinib (45 mg·kg…”
mentioning
confidence: 60%
“…CTCs were defined as mononucleated cells with a surface immunophenotype of CD45 dim/À and ESA þ (30,31). We found that the number of CTCs detected in the blood of the inferior mesenteric vein (mesenteric CTCs) was higher than that of CTCs sampled from the forearm vein (forearm CTCs) in the same patient ( Supplementary Fig.…”
Section: Mesenteric Ctcs Increase and Then Decrease As Crc Advancesmentioning
confidence: 94%
“…One of these challenges is the variability of tumor cell immuno-phenotype during different phases of cancer (progression, metastatic, etc.) which makes the isolation of CTCs very complicated or in some cases, even impossible (Goodale et al, 2009). Furthermore, some tumor cells during the migration to the secondary tissue undergo a process so called epithelial-to-mesenchymal transition (EMT).…”
Section: Isolation and Purification Of Ctcs Using Microchip Technologymentioning
confidence: 99%